Word Formation - Boxadirovna, Feruza Abduraximova; Muslimaxon, Gʼafurova (Journal of Innovation in Education and Social Research, 2024)
Word formation is the process by which new words are created in a language. This article explores the different mechanisms of word formation in English, focusing on derivation, compounding, blending, clipping, borrowing, and conversion. Each process contributes to the development and expansion of a language’s vocabulary. The study of these processes helps linguists understand language evolution and adaptability, as well as the ways people create new meanings in response to cultural, technological, and social changes.